Theory and derivation of unsymmetrical rotor equation of the foil-air bearing rotor system and its validation with experiment data - M. F., Hassan (IOP Publishing, 2019)
This manuscript presents the theory and derivation of rotor equation using rigid body modelling used to validate the modal transformation approach for solving foil-air bearing rotor system. Numerical coefficient of the rotor equation for both methods only different less than 3%. The reasonable correlation in term of orbit’s orientation with experimental data, has proved that the rotor was correctly modelled and adapted with simultaneous solution technique and modal model of foil structure.